KONTRIBUSI PEMBELAJARAN MATEMATIKA DALAM PENGEMBANGAN KARAKTER PESERTA DIDIK YANG BERAKHLAK MULIA - Suparni, Suparni (Universitas Ahmad Dahlan, 2012)
Mathematics education can not be separated from mathematics itself. Therefore, to assess the contribution of learning mathematics in the development of the character of the noble learners would be better if it first revealed the characteristics of the object of abstract mathematics, symbols empty of meaning, agreements and axiomatic deductive reasoning, and anti contradiction. The purpose of mathematics education must consider (1) the formal objectives, namely the arrangement of reason and the formation of the childs personality, and (2) the purpose of any material is the application of mathematics and mathematical skills. Some moral values ??in the learning of mathematics that deals with the characteristics of the mathematics that can be integrated with the Quran include: agreement, ketaatasasan / consistency, deduction, universe. Culture and Education Programme Nation character contains 18 values ??are developed, namely: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of nationalism, patriotism, respect for achievement, friendship / komuniktif, love peace, love reading, environmental care, social care, and responsibility. The development of character morality learners can be achieved by integrating Islamic values ??in the learning of mathematics, namely: the value associated with hablun minallah (relationship of a servant to God), hablun minannas, (relationship with fellow human beings), hablun minannafsi (myself), and hablun minal-alam (relationship with the environment), Keywords: learning math, students character, noble character,